THE ROLE OF THE ANESTHESIOLOGIST IN THE MANAGEMENT OF CRITICALLY ILL SEPTIC PATIENTS: A CLINICAL LITERATURE REVIEW - Maja Osuch,; Maciej Osuch,; Olga Tatarata,; Martyna Jaciubek,; Carmena Luty,; Amanda Abramowicz,; Magdalena Rumin,; Anna Kiełboń,; Zuzanna Olga Reklewska,; Kornelia Domagała, (International Journal of Innovative Technologies in Social Science, 2026)
Sepsis and septic shock are acute, life threatening syndromes in which infection triggers widespread organ dysfunction and rapid clinical deterioration, demanding fast, coordinated action from multiple specialties. In patients who require surgical source control, the anesthesiologist becomes central to perioperative management, because decisions made in the operating room directly influence perfusion, oxygen delivery, and the safety of the procedure. This review focuses on the anesthesiologist’s tasks before, during, and after surgery, with particular attention to how sepsis alters usual anesthetic practice. In unstable patients, careful evaluation of organ failure, cautious choice and dosing of induction drugs (often favoring ketamine or etomidate rather than propofol), advanced monitoring with individually tailored fluid therapy, lung protective ventilation, and timely escalation to vasopressor support are all essential to reduce perioperative risk. Current Surviving Sepsis Campaign recommendations underline that effective source control should be achieved as early as possible, ideally within the first 6 hours from recognizing sepsis, which places anesthesiologists in a key position to balance the urgency of surgery with the need for initial resuscitation. A solid grasp of sepsis pathophysiology and its hemodynamic consequences is therefore fundamental for anesthesiologists involved in the care of these critically ill patients.